An approach for managing the dynamic reconfiguration of software architectures. (2018) - Saadi, Abdelfetah; Oussalah, Mourad Chabane; Henni, Abderrazak
Currently, most software systems have a dynamic nature and need to evolve at runtime. The dynamic reconfiguration of software systems is a mechanism that must be dealt with to enable the creation and destruction of component instances and their links. To reconfigure a software system, it must be stopped, patched and restarted; this causes unavailability periods which are always a problem for highly available systems. In order to address these problems, this paper presents an approach called software architecture reconfiguration approach (SAREA). We define for this approach a set of intelligent agents, each of them has a precise role in the functioning and the control of software. Our approach implements a restoring mechanism of software architecture to a fully functional state after the failure of one or more reconfiguration operations; it also proposes a reconfiguration mechanism which describes the execution process of reconfigurations.